Literature-based Study: The Role of Fintech on MSME Marketing Performance - Mustafa, Muh. Yushar; Shahnyb, Nurafni Shahnyb; Panggabean, Benny Leonard Enrico (Entrepreneurship, Management, and Business Research Journal, 2024)
Studi literatur ini bertujuan untuk mengeksplorasi peranan fintech atau financial technology terhadap performa pemasaran usaha mikro, kecil dan menengah, atau disingkat UMKM, yang sejak kasus pandemi COVID-19 menjadi topik kajian ilmiah menarik untuk diteliti, terlebih lagi di Kota Makassar yang mengalami peningkatan dari sisi laju perekonomian lokalnya. Melalui perspektif perbankan digital, penelitian ini menggunakan analisis performa pemasaran dengan berfokus pada laporan promosi dan penjualan UMKM setelah penggunaan layanan fintech. Sebagai kontribusi secara teoritikal, studi ini pun kemudian menemukan bahwa fintech melalui layanan payment gateway, selain menjadi pendorong dalam perkembangan laju bisnis UMKM, fintech juga berperan positif dan signifikan terhadap kinerja pemasaran UMKM. This literature study aims to explore the role of fintech or financial technology on the marketing performance of micro, small and medium enterprises, or MSMEs for short, has become one of the interesting topics of scientific study to be researched, especially in Makassar City which has a positive trend in its economic level. Through the perspective of digital marketing management, this study uses marketing performance analysis by focusing on the promotion and sales reports of MSMEs after the use of fintech services. As a theoretical contribution, this study then found that fintech through payment gateway services, in addition to being a driver in the development of MSME business rates, fintech also plays a positive and significant role in MSME marketing performance.